Proposal and performance evaluation of an efficient RZ-DQPSK modulation scheme in all-optical OFDM transmission systems - Mirnia, S.E.; Zarei, A.; Emami, S.D.; Harun, Sulaiman Wadi; Arof, Hamzah; Ahmad, Harith; Shalaby, H.M.H. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
A return-to-zero differential quadrature phase-shift keying (DQPSK) modulation scheme is proposed for all-optical orthogonal frequency-division multiplexing transmission systems. The system uses coupler-based inverse fast Fourier transform/fast Fourier transform to support a 700 km single-mode fiber link and a transmission rate of 40 Gb/s without any nonlinear compensation. The performance of the proposed system is evaluated using simulation and four performance measures are obtained, namely, the eye diagram, the eye-opening penalty (EOP), the power spectral broadening, and the bit error rate(BER). The effect of self-phase modulation is taken into account in the performance evaluation. In addition, the performance of the proposed system is compared to that of a traditional one adopting a non-return-to-zero DQPSK scheme. Our results reveal that the proposed system outperforms the traditional one in all four aforementioned performance measures, yet the spectral efficiency is almost preserved. Specifically, for an input average power of 12 dBm, a reduction in both the required optical-signal-to-noise ratio of about 4 dB (to achieve a BER of 10-6) and the EOP of about 5 dB are reported when adopting the proposed system, as compared to the traditional one.